The mechanism of the glycosylase reaction with hOGG1 base-excision repair enzyme: concerted effect of Lys249 and Asp268 during excision of 8-oxoguanine - Šebera, Jakub; Hattori, Yoshikazu; Sato, Daichi; Reha, David; Nencka, Radim; Kohno, Takashi; Kojima, Chojiro; Tanaka, Yoshiyuki; Sychrovský, Vladimír (Nucleic acids research, 2017)
The excision of 8-oxoguanine (oxoG) by the human 8-oxoguanine DNA glycosylase 1 (hOGG1) base-excision repair enzyme was studied by using the QM/MM (M06-2X/6-31G(d,p):OPLS2005) calculation method and nuclear magnetic resonance (NMR) spectroscopy. The calculated glycosylase reaction included excision of the oxoG base, formation of Lys249-ribose enzyme-substrate covalent adduct and formation of a Schiff base. The formation of a Schiff base with ΔG# = 17.7 kcal/mol was the rate-limiting step of the reaction. The excision of the oxoG base with ΔG# = 16.1 kcal/mol proceeded via substitution of the C1΄-N9 N-glycosidic bond with an H-N9 bond where the negative charge on the oxoG base and the positive charge on the ribose were compensated in a concerted manner by NH3+(Lys249) and CO2-(Asp268), respectively. The effect of Asp268 on the oxoG excision was demonstrated with 1H NMR for WT hOGG1 and the hOGG1(D268N) mutant: the excision of oxoG was notably suppressed when Asp268 was mutated to Asn. The loss of the base-excision function was rationalized with QM/MM calculations and Asp268 was confirmed as the electrostatic stabilizer of ribose oxocarbenium through the initial base-excision step of DNA repair. The NMR experiments and QM/MM calculations consistently illustrated the base-excision reaction operated by hOGG1.
Keywords: Guanine; Models, Molecular; lysin; Humans; guanin; Structure-Activity Relationship; vztahy mezi strukturou a aktivitou; Lysine; DNA-glykosylasy; oprava DNA; Mutant Proteins; termodynamika; mutantní proteiny; kyselina asparagová; lidé; molekulární modely; DNA Glycosylases; biokatalýza; DNA Repair; Thermodynamics; protonová magnetická rezonanční spektroskopie; Biocatalysis; Aspartic Acid; Proton Magnetic Resonance Spectroscopy